Penerapan Hukum Terhadap Warga Negara Indonesia Yang Melakukan Tindak Pidana Penyalahgunaan Narkotika Di Luar Negeri - Ciavi Adinda Giantri Katim (Jurnal Hukum Lex Generalis, 2024)
Transnational crime law enforcement Sometimes the perpetrators of the offence to be prosecuted, tried, or executed are not in the territory of the State to carry out the proceedings, but in another State. The objective of the study is to identify and analyze efforts to eradicate drug trafficking in cases of smuggling of smugglers worth 1.7 million Ringgit or the equivalent of Rs. 5.7 billion to Indonesia and to find and analyse the appropriate law enforcement to prosecute cases of the drug traffic. The regulation on drug trafficking in Southeast Asia is considered insufficient to eradicate the black circulation of narcotics in South-East Asia as there are vague norms in law enforcement related to drug problems in ASEAN countries.